Democratization, party systems, and the endogenous roots of Ghanaian clientelism. Issue 1 (2nd January 2020) - Driscoll, Barry
ABSTRACT: Ghana provides an interesting case of a democratic developing country in which clientelism is pervasive yet vote buying is rare. Drawing on fieldwork and recent scholarship, and situated within the comparative frame that animates this special issue, I characterize clientelism in Ghana as party-centred, with resources from the public sector and privately-held commodities, and with significant factionalism within major (party) networks. Building on secondary sources, I explain how the historical development of party and electoral institutions – especially during a period of democratization in the 1990s – enabled Ghana's two main parties to be so central in clientelist politics. Elections are won by either of two quasi-ethnic parties, so campaigns centre around maximizing turnout of likely voters as voters have limited ability to exit their party. Thus, where democratization leads to a strong party system, limited voter mobility may limit individual vote buying. The theoretical implication is that historical moments of institutional creation, rather than the mere institutions themselves, may prove consequential for the varieties of clientelism that endure.